Basic Research Tools for Earthworm Ecology - Kevin R. Butt; Niki Grigoropoulou (Applied and Environmental Soil Science)
Earthworms are responsible for soil development, recycling organic matter and form a vital component within many food webs. For these and other reasons earthworms are worthy of investigation. Many technologically-enhanced approaches have been used within earthworm-focused research. These have their place, may be a development of existing practices or bring techniques from other fields. Nevertheless, let us not overlook the fact that much can still be learned through utilisation of more basic approaches which have been used for some time. New does not always equate to better. Information on community composition within an area and specific population densities can be learned using simple collection techniques, and burrowing behaviour can be determined from pits, resin-insertion or simple mesocosms. Life history studies can be achieved through maintenance of relatively simple cultures. Behavioural observations can be undertaken by direct observation or with low cost webcam usage. Applied aspects of earthworm research can also be achieved through use of simple techniques to enhance population development and even population dynamics can be directly addressed with use of relatively inexpensive, effective marking techniques. This paper seeks to demonstrate that good quality research in this sphere can result from appropriate application of relatively simple research tools.